2020
DOI: 10.1101/2020.06.23.20137521
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS CoV-2 Serosurvey in Addis Ababa, Ethiopia

Abstract: In a serosurvey of asymptomatic people recruited from a clinical laboratory in the general population in May, 2020 in Addis Ababa, Ethiopia three out of 99 persons tested positive for SARS CoV-2 IgG (3.03%, 95% binomial exact confidence interval: 0.63%-8.6%). Taking into account pre-test probability and the sampling scheme, the range of plausible population prevalence values was approximately 1.0-8%. These results suggest that the large majority of the general population in Addis Ababa currently is susceptib… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Furthermore, seroprevalence estimates for SARS-CoV-2 obtained in this study are also comparable with results reported in other African countries during 2020 (although sample period and the testing effort might be different) ( Supplementary Table 1 ). For example, in a serosurvey of asymptomatic people conducted in May 2020 in Addis Ababa (Ethiopia), 3.0% tested positive for SARS-CoV-2 IgG (27). Similarly, a seroprevalence study of 3,098 Kenyan blood donors sampled between April-June 2020 reported a national seroprevalence of 4.3%, with some urban regions reaching around 8% (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, seroprevalence estimates for SARS-CoV-2 obtained in this study are also comparable with results reported in other African countries during 2020 (although sample period and the testing effort might be different) ( Supplementary Table 1 ). For example, in a serosurvey of asymptomatic people conducted in May 2020 in Addis Ababa (Ethiopia), 3.0% tested positive for SARS-CoV-2 IgG (27). Similarly, a seroprevalence study of 3,098 Kenyan blood donors sampled between April-June 2020 reported a national seroprevalence of 4.3%, with some urban regions reaching around 8% (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…13 Besides, as of 10 April 2021, there were 225,516 confirmed COVID-19 cases and 3111 deaths recorded in Ethiopia. 14 Despite that a survey conducted in Addis Ababa suggested that the large majority of the people are susceptible to COVID-19, 15 no data revealed the magnitude of this disease at the community and facility level in the country, even in Africa, with adequate sample size. In addition, a resourcelimited country, such as Ethiopia, might not afford to test all respiratory tract infected patients for SARS-COV-2.…”
Section: Introductionmentioning
confidence: 99%
“…41,42 As a result, SSA countries saw overall lower rates of severe disease in the early stages of the pandemic. [43][44][45] However, following the economic pressure to reopen and relaxation of social distancing measures, infection rates have risen, with seroprevalence estimates in Kenya between 5% for 3174 blood donor samples 46 and 50% for 196 antenatal clinical samples, 47 12.3% among 500 asymptomatic health care workers in Malawi, 48 3% of 99 asymptomatic individuals sampled in Ethiopia, 49 45% in 133 health care workers in Nigeria, 50 Guinea Bissau 18% in 140 health care workers, 51 and 38.5% among 2214 individuals in households in South Sudan. 52 However, in most cases, these estimates are based on studies of target groups, such as health care workers, truck drivers, and small populations of less than 3,000 individuals.…”
Section: Seroprevalence Of Severe Acute Respiratory Syndrome Coronavi...mentioning
confidence: 99%